Tantangan : Implementasi Kebijakan Hukum Restitusi Sebagai Perlindungan Hak Korban Tindak Pidana di Indonesia - Ida Musofiana; Hetiyasari (Fakultas Hukum Universitas Wahid Hasyim, 2024)
The human rights of criminals starting from their status as suspects, defendants, and even convicts are not comparable to the protection of the human rights of victims in order to recover from loss or suffering. The aim of this research is to examine the challenges of implementing policies providing restitution for victims of criminal acts. This research method uses normative juridical, examining aspects of currently applicable legal regulations. This research found that it is important to provide restitution for victims. Considering that so far the victim has only been represented by law enforcement officials. Even though there is a request for compensation by the public prosecutor, not everyone understands the procedure for applying for compensation for a criminal act. Victims really need to receive compensation regardless of age, educational background, and social status.